Cs2CO3-Promoted reaction of tertiary bromopropargylic alcohols and phenols in DMF: a novel approach to α-phenoxyketones - Volostnykh, Ol'ga G.; Shemyakina, Olesya A.; Stepanov, Anton V.; Ushakov, Igor' A. (Beilstein Journal of Organic Chemistry, 2022)
The reaction of bromopropargylic alcohols with phenols in the presence of Cs2CO3/DMF affords α-phenoxy-α’-hydroxyketones (1:1 adducts) and α,α-diphenoxyketones (1:2 adducts) in up to 92% and 24% yields, respectively. Both products are formed via ring opening of the same intermediates, 1,3-dioxolan-2-ones, generated in situ from bromopropargylic alcohols and Cs2CO3.
Keywords: acetylenic alcohol; bromoacetylene; 1,3-dioxolan-2-one; phenols; phenoxyketone